Chemistry textbooks as a means of supporting cognitive activity of general secondary education students - Yaroshenko, О.G. (KU Publ., 2021)
The article is devoted to such new direction of research as creating textbooks that provide competency-based approach to teaching Chemistry. A brief description of the results of the analysis of scientific literature on the research topic is presented. Based on them, it was concluded that it is necessary to develop a concept for creating Chemistry textbooks that would allow realizing the competence potential of academic subject. The main provisions of the author's concept are stated. According to them, the textbook should equally present its content and procedural components, which can ensure the formation of students’ key and subject competencies. The author’s rubrication of the textbooks is presented: “After mastering the material of the unit, you will be able…”, “Remember! Pay attention!”, “Chemistry is life: a naturalist’s page”, “Briefly about the main thing”, “Erudite page”, “Work in groups”, “We work with media sources”, “We know, we understand”, and “We apply”. The design of the units is briefly described. The embodiment of the conceptual provisions in school Chemistry textbooks for grades 8–11 created by the author is revealed on specific examples.
Химия оқулығы жалпы орта білім беру мекемелері оқушыларының танымдық іс-әрекетін ұйымдастырудың құралы ретінде
Учебник химии как средство организации познавательной деятельности учащихся учреждений общего среднего образования
Keywords: author’s concept; Chemistry textbooks; competence-based approach; key competencies; main provisions of the concept; subject competence; textbook content and procedural components; textbook rubrication; unit design